Explore BrainMass

Explore BrainMass

    Exponential equations

    Not what you're looking for? Search our solutions OR ask your own Custom question.

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    Solve for x:

    10^x + 6(10^-x) = 7

    and also:

    3^3x+2 * 8^-x = 4

    © BrainMass Inc. brainmass.com December 24, 2021, 4:41 pm ad1c9bdddf

    Solution Preview

    To simplify the problem,
    let 10^x = y and 10^-x = 1/y
    Therefore, equation becomes: y + 6 (1/y) = 7
    Using a as a common denominator: ...

    Solution Summary

    This shows how to solve exponential equations.